Three-way Subsynchronous Torsional Interactions Between LCC HVDC, MMC HVDC and a Thermal Generator - Stefan Kovacevic; Dragan Jovcic; Pierre Rault; Olivier Despouys (Journal of Modern Power Systems and Clean Energy, 2023)
This paper performs a study on three-way subsynchronous torsional interactions (SSTI) between a hybrid dual-in-feed high-voltage direct current (HVDC) system and a nuclear generator. The test case is based on the French IFA2000 line commutated converter (LCC) HVDC (2 GW) and the new Eleclink modular multilevel converter (MMC) HVDC (1 GW) interacting with the Gravelines generator (1 GW). The analysis is performed by the means of the eigenvalue stability assessment on an analytical model, while the accuracy of the conclusions is verified using the detailed non-linear electromegnetic transient program (EMTP) model. The study shows that the dual-infeed system may introduce higher risk of the SSTI compared with the point-to-point HVDC systems. It shows that MMC operating as static synchronous compensator (STATCOM) may further reduce the torsional damping at 6.3 Hz mode. This conclusion may be unexpected since it is known fact from literature that STATCOM has a beneficial impact on the transient performance of LCC. Further studies show that in a sequential HVDC loading, it may be beneficial to load the MMC HVDC first. Also, the risk of the SSTI may be minimized by changing HVDC controller gains, in particular, by increasing phase-locked-loop (PLL) gains on the LCC rectifier.